1994
DOI: 10.1007/bf03165022
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid imaging in a typical case of acute suppurative thyroiditis with abscess formation due to infection from a persistent thyroglossal duct

Abstract: The clinical evaluation of thyroid imaging with 99mTc, 201Tl, and 67Ga in the uncommon, but potentially serious, disorder of acute suppurative thyroiditis (AST) with abscess formation due to infection from a persistent thyroglossal duct is reported. The 99mTc image showed functioning areas of the diseased thyroid gland and the 201Tl image demonstrated abscess formation in the thyroid gland of this patient. In addition, marked 67Ga accumulation was demonstrated in a wide area covering not only the area of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…A previous report recommended ultrasound-guided fi ne-needle aspiration for evaluation of a focal tender thyroid mass (4) . Thyroid radionuclear imaging can reveal decreased or diminished uptake in the lobe involved (5,13) .…”
Section: Discussionmentioning
confidence: 98%
“…A previous report recommended ultrasound-guided fi ne-needle aspiration for evaluation of a focal tender thyroid mass (4) . Thyroid radionuclear imaging can reveal decreased or diminished uptake in the lobe involved (5,13) .…”
Section: Discussionmentioning
confidence: 98%
“…The results suggest that USguided aspiration with or without lavage had a good treatment effect and without adverse events for the management of AST secondary to PSF. AST occurs mainly in patients with anatomical deformities such as PSF or thyroglossal duct cyst (14). AST also occurs occasionally in patients with diseases such as goiter, malignancies (15,16), and immunodeficiency (17), and occurs rarely in patients undergoing fine needle aspiration (8) or with a history of trauma (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature since her initial presentation have shown that thyroid hormone levels can mimic hyperthyroidism in cases of thyroid suppuration with rises of both total and free T4 and suppression of TSH (Kawanaka et al, 1994;Meier & Nagle, 1996). Reports in the literature since her initial presentation have shown that thyroid hormone levels can mimic hyperthyroidism in cases of thyroid suppuration with rises of both total and free T4 and suppression of TSH (Kawanaka et al, 1994;Meier & Nagle, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…With hindsight, the diagnosis of subacute thyroiditis was wrong. Reports in the literature since her initial presentation have shown that thyroid hormone levels can mimic hyperthyroidism in cases of thyroid suppuration with rises of both total and free T4 and suppression of TSH (Kawanaka et al, 1994;Meier & Nagle, 1996). It has also been reported that steroid administration can relieve pain in both thyroid suppuration and in thyroid cancer (Meier & Nagle, 1996).…”
Section: Discussionmentioning
confidence: 99%